Mathematics 9th (science group) - Dar, H Karamat; Haq -ul- irfan (Caravan book house Lahore, 2023)
- "Caravan Book Mathematics for Class IX - Science Group" is a comprehensive guide tailored specifically for Class IX students studying under the Science Group curriculum. - It covers fundamental mathematical concepts with clarity and precision, ensuring a strong foundation in the subject. - Designed to assist students in mastering mathematical skills and concepts required for academic success in the Science Group stream